2007
DOI: 10.1370/afm.719
|View full text |Cite
|
Sign up to set email alerts
|

Let's Not Talk About It: Suicide Inquiry in Primary Care

Abstract: PURPOSE The purpose of this study was to ascertain physician characteristics associated with exploring suicidality in patients with depressive symptoms and the infl uence of patient antidepressant requests.METHODS Primary care physicians were randomly recruited from 4 sites in northern California and Rochester, NY; 152 physicians participated (53%-61% of those approached). Standardized patients portraying 2 conditions (major depression and adjustment disorder) and 3 antidepressant request types (brand specifi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
106
2
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 39 publications
16
106
2
12
Order By: Relevance
“…Although suicide risk should always be assessed as a routine component of depression evaluation, patients often do not disclose their suicidal thoughts and evidence suggests that primary care providers infrequently ask about suicidality when evaluating depression. 21,22 Using Item 9 from the PHQ-9 does not replace clinical evaluation of suicide risk; however, its use may help primary care providers become more comfortable initiating such discussions. The need for careful suicide risk assessment of all individuals with mental health concerns is underscored by the fact that a small number of individuals reporting SI on Item 9 scored below the threshold on the PHQ-2 and on the PHQ-8.…”
Section: Discussionmentioning
confidence: 99%
“…Although suicide risk should always be assessed as a routine component of depression evaluation, patients often do not disclose their suicidal thoughts and evidence suggests that primary care providers infrequently ask about suicidality when evaluating depression. 21,22 Using Item 9 from the PHQ-9 does not replace clinical evaluation of suicide risk; however, its use may help primary care providers become more comfortable initiating such discussions. The need for careful suicide risk assessment of all individuals with mental health concerns is underscored by the fact that a small number of individuals reporting SI on Item 9 scored below the threshold on the PHQ-2 and on the PHQ-8.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with current suicidal ideation and/or documentation in the medical record of having made a suicide plan or attempt, only one third were referred for consultation. Don'T ASk, Don'T TEll, Don'T knoW Further reinforcing these findings, a 2007 study 30 found only 36% of simulated patients requesting antidepressant medication were even asked about suicide. Patients with simulated major depressive disorder were slightly more likely to be asked, 30 although more than half of these patients were not asked.…”
Section: Primary Care Depression Treatment and Suicidementioning
confidence: 92%
“…Don'T ASk, Don'T TEll, Don'T knoW Further reinforcing these findings, a 2007 study 30 found only 36% of simulated patients requesting antidepressant medication were even asked about suicide. Patients with simulated major depressive disorder were slightly more likely to be asked, 30 although more than half of these patients were not asked. Physician-specific factors that were related to training (eg, time since training) or that could have had a bearing on individual beliefs (eg, sex) did not explain the results.…”
Section: Primary Care Depression Treatment and Suicidementioning
confidence: 92%
See 2 more Smart Citations